Differentiation and characterization of volatile compounds in five common milk powders using HS-GC-IMS, HS-SPME-GC–MS, and multivariate statistical approaches - Yaxi Zhou; Diandian Wang; Jian Zhao; Yu Guo; Wenjie Yan (Food Chemistry: X)
Aroma is a key factor in milk powder quality evaluation and consumer choice. However, research has mostly focused on processing effects, with little on flavor differences among milk powders. This study analysed and identified the flavor characteristics of five common types of milk powders in China, including yak milk powder, donkey milk powder, camel milk powder, goat milk powder, and cow milk powder, using Headspace-Gas Chromatography-Ion Mobility Spectrometry (HS-GC-IMS), Headspace Solid-Phase Microextraction-Gas Chromatography-Mass Spectrometry (HS-SPME-GC–MS), and multivariate statistical analysis. Results identified 55 and 86 volatile compounds via HS-GC-IMS and HS-SPME-GC–MS, respectively, revealing significant differences between milk powders. PCA, OPLS-DA, PLS-DA, and heatmaps further distinguished the sources. Based on VIP values, 27 and 24 key compounds were identified. These results underscored the potential of utilizing these combined techniques for quick flavor analysis and detecting adulteration in milk powder.